The M13 Phage Assembly Machine Has a Membrane-Spanning Oligomeric Ring Structure - Maximilian Haase; Lutz Tessmer; Lilian Köhnlechner; Andreas Kuhn (Viruses, 2022)
Bacteriophage M13 assembles its progeny particles in the inner membrane of the host. The major component of the assembly machine is G1p and together with G11p it generates an oligomeric structure with a pore-like inner cavity and an ATP hydrolysing domain. This allows the formation of the phage filament, which assembles multiple copies of the membrane-inserted major coat protein G8p around the extruding single-stranded circular DNA. The phage filament then passes through the G4p secretin that is localized in the outer membrane. Presumably, the inner membrane G1p/G11p and the outer G4p form a common complex. To unravel the structural details of the M13 assembly machine, we purified G1p from infected E. coli cells. The protein was overproduced together with G11p and solubilized from the membrane as a multimeric complex with a size of about 320 kDa. The complex revealed a pore-like structure with an outer diameter of about 12 nm, matching the dimensions of the outer membrane G4p secretin. The function of the M13 assembly machine for phage generation and secretion is discussed.